Mixed Lineage Kinase 3 phosphorylates prolyl-isomerase PIN1 and potentiates GLI1 signaling in pancreatic cancer development. (1st September 2021) - Viswakarma, Navin; Sondarva, Gautam; Principe, Daniel R.; Nair, Rakesh Sathish; Kumar, Sandeep; Singh, Sunil Kumar; Das, Subhasis; Sinha, Subhash C.; Grippo, Paul J.; Grimaldo, Sam; Giulianotti, Pier Cristoforo; Rana, Basabi; et al.
Abstract: The transcription factor Glioma-Associated Oncogene Homolog 1 (GLI1) is activated by sonic hedgehog (SHH) cascade and is an established driver of pancreatic ductal adenocarcinoma (PDAC). However, therapies targeting upstream hedgehog signaling have shown little to no efficacy in clinical trials. Here, we identify Mixed Lineage Kinase 3 (MLK3) as a druggable regulator of oncogenic GLI1. Earlier, we reported that MLK3 phosphorylated a peptidyl-prolyl isomerase PIN1 on the S138 site, and the PIN1-pS138 translocated to the nucleus. In this report, we identify GLI1 as one of the targets of PIN1-pS138 and demonstrate that PIN1-pS138 is upregulated in human PDAC and strongly associates with the upregulation of GLI1 and MLK3 expression. Moreover, we also identified two new phosphorylation sites on GLI1, T394, and S1089, which are directly phosphorylated by MLK3 to promote GLI1 nuclear translocation, transcriptional activity, and cell proliferation. Additionally, pharmacological inhibition of MLK3 by CEP-1347 promoted apoptosis in PDAC cell lines, reduced tumor burden, extended survival, and reduced GLI1 expression in the Pdx1-Cre x LSL-KRAS G12D x LSL-TP53 R172H (KPC) mouse model of PDAC. These findings collectively suggest that MLK3 is an important regulator of oncogenic GLI1 and that therapies targeting MLK3 warrant consideration in the management of PDAC patients. Highlights: The transcription factor GLI1 has been implicated in PDAC. The MLK3-PIN1 axis regulates GLI1 transcriptional activity. The MLK3 inhibitor, CEP-1347, inhibits GLI1 and reduces the PDAC burden.